Green space influence on thermal comfort contrasting approaches in the assessment of conditions in Bragança (Portugal) - Gonçalves, Artur (2010)
Green Spaces are regarded as elements that can help to provide thermal comfort inside cities. To evaluate this influence both climate and personal variables must be investigated and evaluated taking into account different spatial layouts. Trying to address this complex reality, two different approaches were developed, using green spaces at the city of Bragança (Portugal) as case studies: green spaces surveys, addressing users, and structured experiments, controlling both individual and climatic variables. Field surveys proven to identify a narrow range of thermal sensations, thus limiting the analysis. Data from a structured experiment, conducted in early fall conditions, show the influence of different green space locations on both meteorological variables and thermal sensations. Amongst the evaluated variables, global radiation proves to be the most relevant variable influencing the perceived thermal sensations.